Acceptance is in the eye of the beholder self-esteem and motivated perceptions of acceptance from the opposite sex .[article]. - Cameron, Jessica J.
Social risk self-esteem differences in signature social motivation and behaviors during the relationship initiation process. In particular, the present research tested the hypothesis that lower self-esteem individuals' (LESs) motivation to avoid rejection leads them to self-protectively underestimate acceptance from potential romantic partners, whereas higher self-esteem individuals'(HSEs) motivation to promote new relationships leads them to overestimate acceptance. The results of 5 experiments supported these predictions. Social risk increase activation of avoidance goals for LSEs on a word-recall task but increased activation of approach goals for HSEs, as evidence by their increased use of likeable behaviors. Consistent with these patterns of goal activation, even though actual acceptance cues were held constant across all participants, social risk decreased the amount of acceptance that HSEs perceive from their interaction partner. It is important to note that such self-esteem differences in avoidance goals, approach behaviors, and perceptions of acceptance were completely eliminated when social risk was removed.
Keywords: Self-esteem.; Goals; Motivated perception; Acceptance; Relationship formation